Fine mapping of 14q13 reveals novel variants associated with different histological subtypes of papillary thyroid carcinoma. Issue 3 (3rd December 2018) - Jendrzejewski, Jarosław; Liyanarachchi, Sandya; Eiterman, Andrew; Thomas, Andrew; He, Huiling; Nagy, Rebecca; Senter, Leigha; Sworczak, Krzysztof; de la Chapelle, Albert
Abstract : The first two genome wide association studies (GWAS) of papillary thyroid carcinoma (PTC) detected five variants associated with PTC. Two of them (rs944289 and rs116909374) are located at 14q13 making that locus an important target of research into the genetic predisposition to PTC. We aimed at uncovering other variants at 14q13 associated with PTC independently from the GWAS variants. We performed next generation sequencing of the 14q13 region and analyzed the allele frequencies of single nucleotide polymorphisms (SNPs) in n = 90 PTC cases vs. n = 379 EUR controls from the 1, 000 Genome Project. The variants associated with PTC were validated in an Ohio cohort of n = 1, 216 PTC cases and n = 1, 416 controls. Next, we analyzed the association between SNPs and expression of nearby genes and clinical parameters. We showed that rs368187 was associated with PTC (OR = 1.31, p = 2.20 × 10 −6 ). Rs1632250, Rs1863347 and rs1755787 showed association with classical PTC (cPTC) ( n = 891; OR = 1.24, 2.22 × 10 −3, OR = 1.31, p = 2.15 × 10 −4 and OR = 1.24, p = 2.06 × 10 −3, respectively) while variant rs28397092 showed association with follicular variant ( n = 243; OR = 1.51, p = 1.36 × 10 −3 ). Rs1863347 was associated with suppression of PTCSC3 in unaffected thyroid tissue ( p = 0.026). Rs1632250, rs1863347 and rs1755787 showed association with multifocality (OR = 1.85, p = 0.001, OR = 1.98, p = 0.001 and OR = 1.76, p = 0.003 respectively) and N stage (OR = 1.79, p = 0.014, OR = 1.73, p = 0.023 and OR = 1.81, p = 0.013, respectively) in microPTC ( n = 328) while rs368187 was associated with M stage (OR = 0.56, p = 0.034) in cPTC. Our results disclose multiple variants associated with PTC and clinical features in the 14q13 superlocus. We suggest that translational genotype/phenotype studies should take into account not only somatic mutations but also germline variants. Abstract : What's new? As evidenced by genome‐wide association studies, the 14q13 locus is a hotspot in the genetic predisposition to papillary thyroid carcinoma (PTC). By next‐generation sequencing of the 14q13 region, here the authors uncovered novel single nucleotide polymorphisms (SNPs) that predispose to different histological subtypes of PTC independently of previously‐identified PTC‐associated SNPs located at 14q13. The data demonstrate that germline variants can predispose to PTC by distinct mechanisms, leading to different phenotypic appearances. Based on the findings, the authors also suggest that translational genotype/phenotype studies should consider not only somatic mutations but also germline variants.